TORS elective lingual tonsillectomy has less acute morbidity than therapeutic base of tongue TORS. (June 2021) - Patel, Mihir R.; Ottenstein, Lauren; Ryan, Martha; Farrell, Annie; Studer, Matthew; Baddour, H. Michael; Magliocca, Kelly; Griffith, Christopher; Stokes, William; Switchenko, Jeffrey; Aiken, Ashley; El-Deiry, Mark; et al.
Highlights: Swallow function after TORS for unknown primary is better than tongue base resections. TORS identifies and removes unknown primaries without severely impacting swallow function. Sparing intentional radiation to the primary after TORS for unknown primary is feasible. Abstract: Objective: To determine the impact of diagnostic TORS lingual tonsillectomy (DTLT) on objective swallowing measures for carcinoma of unknown primary (CUP). Methods: Between 10/2016-1/2020, 27 patients with p16+ squamous cell carcinoma (SCC) level 2a nodal disease underwent DTLT and ipsilateral neck dissection for CUP. No patient had a history of cutaneous SCC. Patients participated in Modified Barium Swallow (MBS) three weeks post-TORS, which were then compared to those from a contemporaneous cohort of 40 patients with clinically-identified p16+ base of tongue (BOT) primary tumors. DIGEST scores were retrospectively calculated. Univariate and multivariate analysis performed, stratified by BOT glossectomy (n = 40) versus lingual tonsillectomy for CUP (n = 27). Radiation to the resected primary or potential primary sources was omitted if margins were ≥3 mm or if no primary identified. Results: Twenty-seven consecutive patients with clinical stage cT0N1 HPV-associated OPSCC had a BOT primary pathologically identified in 18/27 (67%). Univariate analysis of functional swallow assessment on MBSImP correlated with improved post-TORS DIGEST scores for CUP. On multivariate analysis (MVA) DIGEST safety scores were improved for CUP than cT1 BOT glossectomy [Odds Ratio (OR) 0.28, p = 0.038]. MVA on matched pT1 CUP (n = 27) vs. pT1 BOT (n = 19), OR of moderate/severe dysphagia for CUP was 0.54 [0.12–2.38, p = 0.417] for DIGEST safety scores and 0.27 [0.06–1.18, p = 0.082] for DIGEST efficiency scores. Moderate/severe dysphagia as determined by DIGEST overall scores for CUP compared to cT1 and pT1 yielded an OR of 0.39 (p = 0.081) and 0.42 (p = 0.195), respectively. Twenty-six total patients received adjuvant RT, and 18 (11 with ≥3 mm margins, 9 with negative specimens) were spared intentional RT to the oropharynx. Median follow-up was 22.6 months with 100% PFS. Conclusions: Patients undergoing DTLT for CUP demonstrated acute swallow defecits in the post-operative setting. A comparison of long-term functional results between DTLT and elective irradiation of the primary site should be studied. Level of evidence: Level III.